Exploring Nextgen Customer Support: How AI is Changing the Game - Sudheer Peddineni Kalava (North American Journal of Engineering Research, 2024)
Exploring Nextgen customer support with AI is crucial in a world where artificial intelligence enhances every aspect of customerservice, from chatbots and virtual assistants to self-service and automation [1] [2] [3]. AI not only streamlines the customer experienceby efficiently answering common questions and guiding customers through processes but also significantly boosts customersatisfaction by offering personalized, proactive services tailored to individual needs and preferences [1] [2]. The advancement of AIin customer support, underscored by an 88% increase since 2020 in the share of service decision-makers utilizing this technology,demonstrates its pivotal role in modernizing customer interactions, enhancing efficiency, and optimizing operations to cater to theever-evolving expectations of customers [1].As this field continues to grow, AI-driven customer support brings forth an array of benefits like heightened agent productivity,intelligent recommendations, and the ability to predict customer behavior, alongside formidable challenges includingimplementation costs and the complexity of training AI models [1] [3]. This article delves into how AI and related technologies suchas natural language processing, supervised learning, and AI customer service solutions are revolutionizing customer service,outlining the tangible benefits, navigating the challenges, and projecting future trends in AI-powered customer support [3] [4].